Single-molecule fluorescence detection of a tricyclic nucleoside analogue. Issue 7 (12th January 2021) - Samaan, George N.; Wyllie, Mckenzie K.; Cizmic, Julian M.; Needham, Lisa-Maria; Nobis, David; Ngo, Katrina; Andersen, Susan; Magennis, Steven W.; Lee, Steven F.; Purse, Byron W.
Abstract : Fluorescent nucleoside analogue ABN is readily detected at the single-molecule level and retains a quantum yield >50% in duplex DNA oligonucleotides. Abstract : Fluorescent nucleobase surrogates capable of Watson–Crick hydrogen bonding are essential probes of nucleic acid structure and dynamics, but their limited brightness and short absorption and emission wavelengths have rendered them unsuitable for single-molecule detection. Aiming to improve on these properties, we designed a new tricyclic pyrimidine nucleoside analogue with a push–pull conjugated system and synthesized it in seven sequential steps. The resulting C -linked 8-(diethylamino)benzo[ b ][1, 8]naphthyridin-2(1 H )-one nucleoside, which we name ABN, exhibits ε 442 = 20 000 M −1 cm −1 and Φ em, 540 = 0.39 in water, increasing to Φ em = 0.50–0.53 when base paired with adenine in duplex DNA oligonucleotides. Single-molecule fluorescence measurements of ABN using both one-photon and two-photon excitation demonstrate its excellent photostability and indicate that the nucleoside is present to > 95% in a bright state with count rates of at least 15 kHz per molecule. This new fluorescent nucleobase analogue, which, in duplex DNA, is the brightest and most red-shifted known, is the first to offer robust and accessible single-molecule fluorescence detection capabilities.